E-business process management technologies and solutions - Sounderpandian, Jayavel; Sinha, Tapen (Idea Group Publishing, 2007)
"This book explores the issues of supply chain management with new perspective providing examples of integrated framework for global SCM, novel ways of improving flexibility, responsiveness, and competitiveness via strategic IT alliances among channel members in a supply chain network, and techniques that might facilitate improved strategic decision making in a SCM environment" - Provided by publisher